2013
DOI: 10.1091/mbc.e13-03-0156
|View full text |Cite
|
Sign up to set email alerts
|

Instantaneous inactivation of cofilin reveals its function of F-actin disassembly in lamellipodia

Abstract: Chromophore-assisted laser inactivation (CALI) was developed to instantly and specifically inactivate cofilin in cells. Simultaneous CALI and live imaging revealed that the principal role of cofilin in lamellipodia at steady state is to break down F-actin, control filament turnover, and regulate the rate of retrograde flow in lamellipodia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 48 publications
4
37
0
Order By: Relevance
“…8). A similar increase in lamellipodial F-actin has been recently described after instantaneous inactivation of cofilin (5). These data suggest that CIN depletion enhanced P-cofilin levels that led to a decrease in filament disassembly.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…8). A similar increase in lamellipodial F-actin has been recently described after instantaneous inactivation of cofilin (5). These data suggest that CIN depletion enhanced P-cofilin levels that led to a decrease in filament disassembly.…”
Section: Discussionsupporting
confidence: 86%
“…C ofilin is one crucial mediator of actin cytoskeletal dynamics during cell motility (1)(2)(3)(4)(5). At the cell edge, cofilin severs F-actin filaments, generating substrates for Arp2/3-mediated branching activity and contributing to F-actin depolymerization by creating a new pointed end and F-actin assembly by increasing the pool of polymerization-competent actin monomers (G-actin) (6,7).…”
mentioning
confidence: 99%
“…Two possible solutions to this paradox have been proposed: (1) cofilin-mediated severing might create free barbed ends and polymerizing actin filaments that can activate the Arp2/3 complex , and (2) SPIN90 (also known as NCKIPSD)-mediated activation of the Arp2/3 complex without pre-existing actin filaments (Wagner et al, 2013). However, neither mechanism seems to be satisfactory as knockdown and CALI of cofilin results in enlargement of lamellipodia and ruffles and increased F-actin levels in cells employing the mesenchymal mode of migration (Hotulainen et al, 2005;Rogers et al, 2003;Sidani et al, 2007;Vitriol et al, 2013), and full-length SPIN90 does not activate the Arp2/3 complex (Fukuoka et al, 2001 and data not shown). In this regard, the involvement of another actin nucleator in the mechanism regulating initial activation of the Arp2/3 complex would resolve this paradox.…”
Section: Discussionmentioning
confidence: 99%
“…Without changing the localization of the actin regulator cofilin, CALI was performed separately in cofilin-depleted cells by using KillerRed coupled to either a constitutively active cofilin mutant (cofilin S3A ) or a dominantnegative cofilin mutant (cofilin S3E ) (Vitriol et al, 2013). Cells that express either cofilin S3A or cofilin S3E fused to KillerRed show no obvious change in the quantity or distribution of lamellipodial F-actin.…”
Section: Cali With Killerredmentioning
confidence: 99%